Mitigation of negative impedance instabilities in DC distribution systems : a sliding mode control approach - Fulwani, Deepak Kumar; Singh, Suresh (Springer, 2016)
This book focuses on the mitigation of the destabilizing effects introduced by constant power loads (CPLs) in various non-isolated DC/DC converters and island DC microgrids using a robust non-linear sliding mode control (SMC) approach. This book validates theoretical concepts using real-time simulation studies and hardware implementations. Novel sliding mode controllers are proposed to mitigate negative impedance instabilities in DC/DC boost, buck, buck-boost, bidirectional buck-boost converters, and islanded DC microgrids. In each case, the condition for the large-signal stability of the converter feeding a CPL is established. An SMC-based nonlinear control scheme for an islanded DC microgrid feeding CPL dominated load is proposed so as to mitigate the destabilizing effect of CPL and to ensure system stability under various operating conditions. A limit on CPL power is also established to ensure system stability. For all proposed solutions, simulation studies and hardware implementations are provided to validate the effectiveness of the proposed sliding mode controllers.
Keywords: Electric power distribution -- Direct current.; Sliding mode control.; elektronické knihy; electronic books